Análise jurídico-econômica do big personal data como um ativo econômico intangível das empresas - Serro, Bruna Manhago (Universidade do Vale do Rio dos Sinos, 2021)
The present study addresses the legal aspects of the set of personal data that companies have with regard to their business relationships, from the standpoint of an intangible economic asset to integrate the assets of these companies. The research aims to demonstrate that existing theoretical concepts for intangible assets can be applied to personal databases without confronting data protection legislation, as long as the treatment is carried out properly. The methodology used was the resolution of a problem, through the bibliographical review of the concepts of personal data and the new obligations for legality in its treatment, according to the provisions of Law n. 13.709/18 (General Law of Brazilian Data Protection – LGPD) and some application criteria of the Regulation no. 2016/679 (General Regulation on Data Protection – European Union), as well as the subsequent confirmation of the hypotheses raised through applied qualitative research. As a conclusion of the research, the theoretical adequacy test for personal databases as intangible assets was verified, as well as the companies intention to take advantage, when necessary, of this accounting recognition and its economic benefits.
Keywords: Bancos de dados; Dados pessoais; Ativos intangíveis; Databases; Personal data; Intangible assets; ACCNPQ::Ciências Sociais Aplicadas::Direito